Use of melatonin: a single-centre audit - Joanna J Garstang; Rebecca Dack (BMJ Publishing Group, 2022)
Sleep disorders in childhood are common. Melatonin is prescribed by UK community paediatricians to treat sleep disorders, but practice is not standardised. This audit reviewed melatonin prescribing within a community paediatric department in a 12-month period. 682 children received melatonin prescriptions; a random sample of 198 records were reviewed. The most common underlying condition was autism spectrum disorder (ASD) in 28%. 41% had no underlying diagnosis when melatonin was initiated and were waiting for neurodevelopmental/ASD assessment. 42% were on melatonin for at least 2 years. Further work is required to optimise melatonin prescribing practice for children and young people.